KONTRIBUSI SEKTOR PERTANIAN TERHADAP PEREKONOMIAN KABUPATEN BREBES - Khusnul Khatimah; Siti Mudmainnah (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the economic sector and the agricultural sector basis, determine sub-sector basis in the agricultural sector which has fast growth and competitiveness both, and as well as knowing the agricultural sector income multiplier in Brebes. The basic method used in this research is descriptive. The data used are secondary data. Method of data analysis used are LQ, shift share and income multipliers. The results showed the agricultural, forestry and fisheries sectors is a sector basis. Horticultural crops sub sector, agriculture and hunting services sub sector and the forestry sub sector is a sub sector basis. Sub sector, which has a rapidly growing sub sector are horticultural crops, livestock, plantation and agriculture and hunting services sub sector. Sub sector that are competitive both sub sector are food crops, forestry, agriculture and hunting services, plantation and fisheries sub sector. Agricultural income multiplier for the year 2016-2020 had an average value of 2,8540, meaning that every happened increase agricultural incomes by Rp 1 then going to increase total revenue of Rp 2,8540.